2018
DOI: 10.1177/000313481808400430
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Functional Outcomes after Blunt Cerebrovascular Injury: A 20-Year Experience

Abstract: Since blunt cerebrovascular injury (BCVI) became increasingly recognized more than 20 years ago, significant improvements have been made in both diagnosis and treatment. Little is known regarding long-term functional outcomes in BCVI. The purpose of this study was to evaluate the impact of BCVI on those long-term outcomes. All patients with BCVI from 1996 to 2014 were identified from the trauma registry. Functional outcome was measured using the Boston University Activity Measure for Post-Acute Care. Multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…66 Previous studies have demonstrated the importance of stroke prevention as a key factor in improving long-term functional outcomes following BCVI, but optimal antithrombotic choice remains unknown. 48,67,68 In our systematic review and meta-analysis, we similarly found that the ischemic stroke rate in previously asymptomatic patients was not significantly different between AP versus anticoagulation treatment. Direct meta-analysis comparison between the untreated patients versus patients treated with any antithrombotic was not performed because multiple studies have already confirmed the benefit of antithrombotic treatment, and our systematic review was not designed to capture these studies.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…66 Previous studies have demonstrated the importance of stroke prevention as a key factor in improving long-term functional outcomes following BCVI, but optimal antithrombotic choice remains unknown. 48,67,68 In our systematic review and meta-analysis, we similarly found that the ischemic stroke rate in previously asymptomatic patients was not significantly different between AP versus anticoagulation treatment. Direct meta-analysis comparison between the untreated patients versus patients treated with any antithrombotic was not performed because multiple studies have already confirmed the benefit of antithrombotic treatment, and our systematic review was not designed to capture these studies.…”
Section: Discussionmentioning
confidence: 53%
“…Antiplatelet drug resistance or lack of response to agents such as aspirin or clopidogrel may be detected by platelet function testing and has been shown to predict an increased risk of ischemic events while on AP treatment 66 . Previous studies have demonstrated the importance of stroke prevention as a key factor in improving long-term functional outcomes following BCVI, but optimal antithrombotic choice remains unknown 48,67,68 …”
Section: Discussionmentioning
confidence: 99%
“…1 While the injury is rare, 2-4 resulting stroke can have devastating consequences for the patient. 5 BCVI is treated with antithrombotic or anticoagulant therapy, which have been shown to decrease stroke rates in patients with BCVI. 3,4,6-12 However, BCVI in the setting of TBI is challenging as there is concern for hemorrhagic progression with BCVI treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Shahan et al demonstrated that stroke, along with age, predicts decreased mobility after BCVI and that the occurrence of stroke predicts decreased activity and cognitive function. 17 Given the association of BCVIs with traumatic brain injury, functional and cognitive impairment may be further exacerbated in the elderly in whom falls are common.…”
Section: Introductionmentioning
confidence: 99%